Analisis Pengembangan Kompetensi Tenaga Pendidik dalam Strategi Kepala Sekolah di SD Negeri Kedurus 1 Surabaya - Rahayu, Aulia Sagita; Aisyah, Nesha (ARZUSIN, 2023)
Teachers who are competent will be able to teach their students effectively and efficiently. The demand for higher-quality education is growing in the digital and information era, so efforts must be made to improve educators' competence in order to provide high-quality instruction. This research aims to analyze the development of teacher competence at SDN Kedurus 1 Surabaya. The type of research used a descriptive qualitative research. Data collection tools use interviews, documentation, and observation as well as literature revoiews through several journals that are databases on Google Scholar. Based on interviews with school principals, it was found about how the competence development program for educators at this school. This research is to observe, analyze, and prove about the educator competency development program implemented in the school. The result of the study revealed that the competency development carried out was good. Envidence by the principal who includes the role of educators in organizing it. The pricipal involves educators in development programs held by the agency such as training, seminars, and MGMP. Furthermore, obstacles in the development process are still encountered by educators with limited use of technology. Therefore, the role of the principal here is also as a motivation for educators, so that they can improve their abilities so that they are not outdate. The competency development model for the future, according to the principal, is often participating in training or workshops whose purpose is to better condition teachers to be able to keep up with the times and accompany to share knowledge about character education with student.